Project-Based Learning in Higher Vocational Education: Bridging English Communication and Digital Marketing Competencies - Agustina Hananingsih (EDUPEDIA Publisher, 2026)
Purpose – This study aims to investigate the impact of implementing digital business project-based learning (PjBL) on vocational accounting students’ English proficiency, engagement, and collaborative skills. The background of this study is rooted in the urgent need to align English for Specific Purposes (ESP) instruction with the demands of the modern digital economy, where graduates are expected to possess not only technical accounting expertise but also cross-functional communication and digital literacy skills. Methodology – This study employed a mixed-methods sequential explanatory design. The sampling design involved purposive sampling, with a total sample size of 33 students from the Managerial Accounting program. The research procedure consisted of an intervention phase where students participated in a digital marketing project, followed by data collection using a closed-ended questionnaire to measure perceptions and semi-structured interviews for in-depth qualitative insights. Data were analyzed using descriptive statistics to interpret numerical trends and thematic analysis to identify recurring patterns in students’ experiences. Findings –The study reveals that digital business PjBL significantly enhances student motivation, vocabulary acquisition, and communicative confidence, with an overall domain mean score exceeding 3.90. Findings indicate that authentic digital production shifts students from passive learners to active creators, fostering professional communication skills. However, the study also identifies challenges such as logistical coordination and unequal workload distribution within collaborative groups. It is concluded that while PjBL is an effective pedagogical strategy for vocational education, its success relies on structured individual accountability systems and robust instructor scaffolding to balance technical and linguistic demands. Novelty – The originality of this research lies in its integration of professional digital marketing content creation into the specific context of an Applied Bachelor of Managerial Accounting curriculum. Unlike conventional ESP studies that focus on general communication, this research provides a framework for embedding automated commercial ecosystems and digital literacy into vocational language training, bridging the gap between classroom theory and real-world industrial expectations. Significance – This study provides valuable insights for ESP practitioners, vocational lecturers, and curriculum developers in higher education institutions. By offering a proven framework for digital project-based instruction, this research serves as a guideline for optimizing lecturer competency development and fostering student readiness for the digitized global workplace.